2022
DOI: 10.1111/bcp.15204
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of neutrophil–lymphocyte ratio in the relationship between ondansetron pre‐treatment and the mortality of ICU patients on mechanical ventilation: Causal mediation analysis from the MIMIC‐IV database

Abstract: Aims The mortality of critically ill patients undergoing mechanical ventilation (MV) is high and few strategies are available. We explored the relationship between ondansetron pre‐treatment, the neutrophil–lymphocyte ratio (NLR), and platelet–lymphocyte ratio (PLR), and mortality of ventilated patients in the intensive care unit. Methods We developed a retrospective cohort study that involved patients undergoing MV in the Multiparameter Intelligent Monitoring in Intensive Care IV (MIMIC‐IV) database. Causal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The beneficial effects of 5-HT3 receptor antagonists have also been seen on anti-inflammation ( 9 12 ), renal function ( 13 15 ), and even mortality reduction ( 16 20 ). Recent retrospective studies reported an association between ondansetron use and reduced risk of mortality in critically ill patients both with and without acute kidney injury (AKI) ( 17 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects of 5-HT3 receptor antagonists have also been seen on anti-inflammation ( 9 12 ), renal function ( 13 15 ), and even mortality reduction ( 16 20 ). Recent retrospective studies reported an association between ondansetron use and reduced risk of mortality in critically ill patients both with and without acute kidney injury (AKI) ( 17 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of 5-HT3 receptor antagonists have also been seen on anti-inflammation ( 9 12 ), renal function ( 13 15 ), and even mortality reduction ( 16 20 ). Recent retrospective studies reported an association between ondansetron use and reduced risk of mortality in critically ill patients both with and without acute kidney injury (AKI) ( 17 20 ). Patients undergoing cardiac surgery are also at high risk of developing AKI ( 21 ), but research on the mortality benefit of ondansetron use in cardiac surgical patients is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sub-group analysis of our study indicated that ondansetron treatment was significantly associated with the mortality of moderate-to-severe TBI patients but not mild TBI patients. The effect of ondansetron on the mortality outcome has also been verified among other kinds of critically ill patients, including those diagnosed with acute kidney injury, COVID-19, or undergoing cardiac surgery ( Bayat et al, 2021 ; Tao et al, 2021 ; Fang et al, 2022 ; Gray et al, 2022 ; Xiong and Xiong, 2022 ; Zhou et al, 2022 ). This beneficial influence may not only depend on the antiemetic effect but also on other effects of ondansetron, including anticoagulation, regulation of inflammation and immune status, renal protection, and neuroprotection ( Fakhfouri et al, 2012 ; Liu et al, 2012 ; Sharma et al, 2019 ; Wu et al, 2019 ; Guo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 87%
“…As a serotonin 5-hydroxytryptamine (5-HT3) receptor antagonist, ondansetron is commonly used for preventing and alleviating nausea and vomiting in patients receiving radio-chemotherapy or undergoing surgery. In addition to decreasing vomit-related complications, ondansetron has also been verified to improve the prognosis of critically ill patients, including those confirmed with acute kidney injury, coronavirus disease 2019 (COVID-19), or undergoing cardiac surgery ( Bayat et al, 2021 ; Tao et al, 2021 ; Fang et al, 2022 ; Gray et al, 2022 ; Xiong and Xiong, 2022 ; Zhou et al, 2022 ). Some studies have confirmed the pleiotropic effects of ondansetron, including anticoagulation, regulation of inflammation and immune status, renal protection, and neuroprotection ( Fakhfouri et al, 2012 ; Liu et al, 2012 ; Sharma et al, 2019 ; Wu et al, 2019 ; Guo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some indicators reflecting the level of systemic inflammation, including neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR), were highly correlated with mortality in septic patients ( Kaushik et al., 2018 ; Shen et al., 2019 ; Huang et al., 2020 ). Interestingly, researchers found that OND pre-treatment decreased the mortality of ICU patients on mechanical ventilation, which could be explained by regulation of NLR ( Zhou et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%